Evaluasi Tata Kelola Penambangan Sirtu Berbasis Good Mining Practice - Dwi Eri Yanti; Vera Surtia Bachtiar; Alfirmansyah Alfirmansyah; Ummi Jayanti (Fakultas Teknik Universitas Cenderawasih, 2026)
The governance of sand and gravel mining requires an integrated assessment of technical planning, occupational safety, environmental control, reclamation, and regulatory compliance. This study evaluated the governance of CV. Ria Bersaudara, a sand and gravel mining company located in Pasar Surulangun, Rawas Ulu District, Musi Rawas Utara Regency, using the Good Mining Practice framework. The study used a descriptive evaluative approach based on field observation, document review, indicative resource estimation, equipment productivity analysis, occupational safety and environmental risk assessment, and compliance mapping. The results show that the company has a basic legal foundation through an exploration mining permit covering 12.5 ha; however, several governance components require improvement. The indicative prospective area was approximately 2.50 ha, with an effective follow-up area of 1.80 ha and an estimated indicative resource of 21,600 m³ or 35,640 tons. Productivity analysis indicated that excavator capacity reached about 61 m³/hour, while one dump truck only transported about 10.3 m³/hour, creating a haulage bottleneck if the truck fleet is insufficient. Safety implementation was also not optimal, with personal protective equipment compliance estimated at only 55%. The study recommends validating permit documents, strengthening technical exploration data, improving drainage and sediment control, enforcing safety procedures, implementing progressive reclamation, and establishing daily operational records.